Red blood cell transfusion in critically-ill children and its association with outcome - Hafsa Sohail; Shah Ali Ahmed; Parveen Usman; Farah Khalid; Anwar ul Haque; Qalab Abbas (Journal of the Pakistan Medical Association, 2021)
Published in August 2021